The Maroon Communitarion Dilemma: Navigating the Intersices between Resistance and Collaboration - Robert Connell (Caribbean Studies Students' Union, 2012)
Robert Connell earned his Bachelor of Environmental Studies degree with honors and a minor in Political Science from York University in 2009. He is currently a PhD student at the University of California, Berkeley in African Diaspora Studies. His research focuses on conflicts over resource extraction and sovereignty rights between Maroons and the Jamaican state in the 21st century. His corollary research interests include indigeneity and indigenous struggle, development studies, ethnic multiplicity in the African Diaspora, global environmental politics and ecological economics.